Low temperatures in food technologies - Simahina, Galina (My University, 2013)
The products obtained with cryogenous technology аre outstanding due to their high quality, positive influence on human organism’s organs and functions, the ability to avoid accumulating radionuclides and other toxic substances and, otherwise, to remove those present in the organism.
Keywords: cryogenous technology; biological activity; freezing; cooling agents; powders; radionuclides; quality; safety; кріотехнологія; біологічна активність; заморожування; холодоагенти; порошки; радіонукліди; якість; безпека; криотехнология; биологическая активность; замораживание; хладагенты; порошки; радионуклиды; качество; безопасность; кафедра технології оздоровчих продуктів